The language in blind children and the question about autistic-Iike features - Pérez Pereira, Miguel (2000)
Hobson et al. (Brown, Hobson. Lee y Stevenson, 1997; Hobson, Brown, Minter y Lee, 1997)ha ve updated the issue of the similarities between autism and congenital blindness. In the pre sent paper the empirical evidence in favor of the existence of autistic-lik features in the lan guage of blind children is reviewed. and new data from the author's research, are offered. The following topics are examined: (a) The use of personal pronouns, (b) the use of imitations and formulaic speech, (e) the egocentric use of speech, and (d) the capacity for iniciating conver sations and for conversational contingency. The analysis puts into question the similarity bet ween blind children and autistic children, and seems to disconfirm Hobson 's theory.